Bandung Sadayana: Partisipasi Digital Masyarakat Kota Bandung dalam Membangun Smart City - Putri Haryani; Naila Triandaya Putri; Lina Miftahul Jannah (VISA: Journal of Vision and Ideas, 2024)
The digital era has changed interactions between government and society, especially through wider digital participation and easy access through digital media. Community participation in this context can take the form of decision analysis, involving a process of deliberation and decision structuring to understand community preferences and perspectives. However, this participation is often limited to the later stages of the policy cycle, reducing the public's contribution to policy formation. This research focuses on the digital participation of the people of Bandung City, which is increasingly active through initiatives such as Bandung Sadayana. This platform, through features like Badami Forum, enables citizens to contribute to the development of the city. In the context of smart city development, Bandung faces challenges such as uneven socialization, lack of understanding of the smart city roadmap, and limited infrastructure. The effectiveness of community participation is influenced by a number of factors, including active involvement in planning forums, information transparency, effective communication, and the quality of policy implementation. Recommendations involve expanding digital participation through outreach campaigns, increasing transparency and communication, and focusing on the quality of project implementation.